The impact of COVID-19 pandemic on invasive fungal infections in Africa: What have we learned? - Chibuike Ibe (Public Library of Science (PLoS), 2022)
Invasive fungal infections (IFIs) have been described as diseases of the poor. The mortality rate of the infections is comparable to that of malaria, HIV, and TB, yet the infections remain poorly funded, neglected in research, and policy at all levels of human resources. The Coronavirus Disease 2019 (COVID-19) pandemic has further worsened the current state of management for IFIs. At the same time, response to COVID-19 has stirred and boosted vaccine production, vaccine substance manufacturing, and building of next-generation sequencing capacity and genomics data sharing network in the continent. Through collaboration and transdisciplinary research effort, these network and technology can be extended to encourage fungal research to address health issues of existing and emerging fungal pathogens.